Comparison of Knotless and Knotted Single-Anchor Repair for Ruptures of the Upper Subscapularis Tendon: Outcomes at 2-Year Follow-up. Issue 3 (15th March 2022) - Sgroi, Mirco; Kranz, , Marilena; Seitz, Andreas Martin; Ludwig, Marius; Faschingbauer, Martin; Zippelius, Timo; Reichel, Heiko; Kappe, Thomas
Background: Both knotted and knotless single-anchor repair techniques are used to repair transmural ruptures of the upper subscapularis (SSC) tendon. However, it is still unclear which technique provides better clinical and radiological results. Purpose/Hypothesis: To compare the clinical and magnetic resonance imaging (MRI) outcomes of knotless and knotted single-anchor repair techniques in patients with a transmural rupture of the upper SSC tendon at 2-year follow-up. It was hypothesized that the 2 techniques would not differ significantly in outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: Forty patients with a transmural tear of the upper SSC tendon (grade 2 or 3 according to Fox and Romeo) were retrospectively enrolled. Depending on the repair technique, patients were assigned to either the knotless single-anchor or knotted single-anchor group. After a mean follow-up of 2.33 ± 0.43 years, patients were assessed by the ASES, WORC, OSS, CS, and SSV. A clinical examination that included the bear-hug, the lift-off, and the belly-press tests was performed, in which the force exerted by the subjects was measured. In addition, all patients underwent MRI of the affected shoulder to assess repair integrity, tendon width, fatty infiltration, signal-to-signal ratio of the upper and lower SSC muscle, and atrophy of the SSC muscle. Results: No significant difference was found between the 2 groups on any of the clinical scores [ASES ( P = .272), WORC ( P = .523), OSS ( P = .401), CS ( P = .328), SSV ( P = .540)] or on the range-of-motion or force measurements. Apart from a higher signal-to-signal ratio of the lower SSC muscle in the knotless group ( P = .017), no significant difference on imaging outcomes was found between the 2 groups. Conclusion: Both techniques can be used in surgical practice, as neither was found to be superior to the other in terms of clinical or imaging outcomes at 2-year follow-up.